Potencial de captura de carbono de la Guadua spp, por estadíos en el bosque local “El Maronal de Atumplaya” - Aguirre Mori, David Armando (2009)
For the sake of determining the quantity of carbon captured at the Big Sea's different stadiums (Guadua spp.) At the Local Forest Atumplaya's Maronal, you calculated the aerial total biomass and his distribution for components (stem, branches and sheets), at an adult plantation that you date since 1930 and that as of the present moment is being recovered and driven of sustainable way by the local settlers; Using equations alométricas logarithmic of the shape And a (THEY GIVE). Two forestal censuses (2008 and 2009) in two of the four barracks that the Maronal (barracks 1 and 111) because the representatives of the structure of the barracks are 11 and IV comprises were accomplished. Taking a sample of like base nineteen culmos (the big sea's complete stems) for each growth stage (sprout, green and ripe plantain), a destructive sampling to determine the overall length of the culmo, the humidity content, the volume carne true, he weighed cool of every culmo and your components and the aerial total biomass. In the theoretical phase one for each stadium, all the components obtained three equations themselves they had coefficient of determination (R2 ) bigger to O, 79 and the half a square ofthe error (CME) was minor to 0,055 in the elected equations. The average biomass obtained at each stadium belonged to 29.83 in-bud Kg (27,35 kg, at branches and 2,48 kg. at foliage), 49,65 kg. in greens (40,04 kg. in stem, 6,75 kg. at branches and 2,86 kg. at foliage), and 47,76 kg. in ripe plantains (40,52 kg. in stems, 5,57 kg. at branches and 1,68 kg. at foliage). The Total Biomass obtained at 6.31 forest are he was of 407.34 Ton in the year 2008 and 506.14 Ton in the year 2009, with 98.8 ton's increment ofbiomass ayear; What is equivalent to 44.462 C's ton year in the whole the plantation and 7.046 tons of carbon There Is year. The capture ofatmospheric C02 is of 163.027 Ton ofC02 in one year and once aerial (culmo, branches and sheets) Guadua's biomass was brought over to spp.; That you represent 25.836 Ton of C02/Ha year. vi The use of the ripe stems of big sea at the construction of houses implies that the biomass can be transferred to a reserve with a period of average residence of 80 years with the adequate treatment.